2022
DOI: 10.1177/1742271x221131282
|View full text |Cite
|
Sign up to set email alerts
|

Australian sonographers’ perceptions of patient safety in ultrasound imaging: Part two – translation into practice

Abstract: Introduction: A lack of patient safety research hampers capacity to improve safety in healthcare. Ultrasound is often considered ‘safe’ as it does not use ionising radiation, a simplistic view of patient safety. Understanding sonographers’ actions towards patient safety is crucial; however, self-reported measures cannot always predict behaviour. This study is part of a PhD exploring patient safety in medical diagnostic ultrasound. The aim of this paper is to explore sonographers’ responses to the patient safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…This is the primary risk to developing embryos and babies [ [60] , [61] , [62] , [63] ]. Animal research using both non-ultrasound and ultrasound technologies has shown that maternal heat exposure is hazardous to the developing embryo/fetus [ 60 , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. It seems to be the case if the temperature increases by more than 1.5 °C over the physiological threshold.…”
Section: Methodsmentioning
confidence: 99%
“…This is the primary risk to developing embryos and babies [ [60] , [61] , [62] , [63] ]. Animal research using both non-ultrasound and ultrasound technologies has shown that maternal heat exposure is hazardous to the developing embryo/fetus [ 60 , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. It seems to be the case if the temperature increases by more than 1.5 °C over the physiological threshold.…”
Section: Methodsmentioning
confidence: 99%